Evidence for the role of corticotropin-releasing factor in major depressive disorder. (November 2015) - Waters, R. Parrish; Rivalan, Marion; Bangasser, D.A.; Deussing, J.M.; Ising, M.; Wood, S.K.; Holsboer, F.; Summers, Cliff H.
Highlights: Central CRF systems play a pivotal role in susceptibility to social stress. Sex differences in central CRF reflect observed sex differences in depression. CRF interacts with other brain systems to influence stress susceptibility. Targeting central CRF may be a useful strategy to treat depression in some patients. Abstract: Major depressive disorder (MDD) is a devastating disease affecting over 300 million people worldwide, and costing an estimated 380 billion Euros in lost productivity and health care in the European Union alone. Although a wealth of research has been directed toward understanding and treating MDD, still no therapy has proved to be consistently and reliably effective in interrupting the symptoms of this disease. Recent clinical and preclinical studies, using genetic screening and transgenic rodents, respectively, suggest a major role of the CRF1 gene, and the central expression of CRF1 receptor protein in determining an individual's risk of developing MDD. This gene is widely expressed in brain tissue, and regulates an organism's immediate and long-term responses to social and environmental stressors, which are primary contributors to MDD. This review presents the current state of knowledge on CRF physiology, and how it may influence the occurrence of symptoms associated with MDD. Additionally, this review presents findings from multiple laboratories that were presented as part of a symposium on this topic at the annual 2014 meeting of the International Behavioral Neuroscience Society (IBNS). The ideas and data presented in this review demonstrate the great progress that has been made over the past few decades in our understanding of MDD, and provide a pathway forward toward developing novel treatments and detection methods for this disorder.